Transnational Social Spaces And Diasporic Publics. How Migrants Are Changing Traditional Conceptualisations Of The Public Sphere - Marino, Sara (AoIR Selected Papers of Internet Research, 2017)
This paper addresses the emergence of diasporic networked publics as a result of changing patterns of international migration on the one hand, and the configuration of transnational social spaces challenging traditional notions of the public sphere on the other hand. Drawing on a three-year online ethnography seeking to explore how Italian migrants in London use and consume digitally networked technologies, it will be argued that migrant networks can be interpreted as constituting a transnational social field created by a network of networks, where new reconfigurations of the idea of public space are taking place. In particular, the paper addresses the following questions: how is connectivity transforming the way diasporic identities and communities are formed? How and to what extent do digital media affect and facilitate the formation of transnational online publics, while supporting adaptation to the host society and an on-going dialogic bridge with home? What can digital diasporas tell us about the transformation of public space in the Digital Age? Preliminary findings suggest that online diasporic spaces act as: - Polycentric and polycephalic webs of solidarity and support where specific nodes (long term migrants) exercise more influence than others; - Spaces where emotional connections are established among migrants, with the purpose of overcoming social isolation and of coping with a sense of de-territorialisation; - Spaces where traditional notions of public and private blur as users share personal experiences and private information (e.g. home address) in a fundamentally public space, as membership is not required to read users’ conversations.